(untitled) (European Journal of Formal Sciences and Engineering, 2021)
The dimensional stability and durability of Acrylamide- and Methacrylate-based acrylic resins have been studied. The dimensional stability was characterized by measuring the volume expansion of samples immersed in water for a period up to 240 days or by exposing the samples to 23oC and 50 per cent, 90 per cent relative humidity and by monitoring the shrinkage. The durability was investigated by exposing the resins to cyclic variations of temperature in air and in water. The resins generally exhibit a significant volume change up to 160 per cent of the initial volume when immersed in water or exposed to a relatively dry atmosphere (23oC and 50 per cent). A general increase in the material stiffness and/or crack formation on the surface of the resin is observed. On a long-term basis, the durability of the resins may significantly vary with occasionally a partial or complete deterioration of the some resins. A general better dimensional stability and durability is observed for the Methacrylate-based resins as compared to the Acrylamide-based resins.